2021
DOI: 10.1097/wno.0000000000001408
|View full text |Cite
|
Sign up to set email alerts
|

Anemia and Idiopathic Intracranial Hypertension: A Systematic Review and Meta-analysis

Abstract: Background:Idiopathic intracranial hypertension (IIH) is a condition typically affecting young, obese women. Although anemia is recognized as a risk factor of IIH from case reports, their relationship remains controversial as several comparative studies showed no significant association. This study aimed to examine the relationship between anemia and IIH.Methods:MEDLINE, Embase, Cochrane Library, and grey literature were searched to September 2020. Primary studies on patients with diagnoses of anemia of any ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 39 publications
1
23
0
Order By: Relevance
“…3 Our group performed a systematic review of the literature and identified 74 cases of IIH reported in the literature that were associated with anemia, with only 16 of these patients reported to be obese. 4 The most common causes of anemia were iron deficiency. In 60% of cases, anemia treatment without ICP-lowering therapy was initiated and patients demonstrated improvement or resolution of symptoms.…”
mentioning
confidence: 99%
“…3 Our group performed a systematic review of the literature and identified 74 cases of IIH reported in the literature that were associated with anemia, with only 16 of these patients reported to be obese. 4 The most common causes of anemia were iron deficiency. In 60% of cases, anemia treatment without ICP-lowering therapy was initiated and patients demonstrated improvement or resolution of symptoms.…”
mentioning
confidence: 99%
“…A cross-sectional study by Ardissino et al (7) found a statistically higher prevalence of anemia in IIH patients compared with controls. This finding was supported in a meta-analysis carried out by Yu et al (8) Despite the existing literature supporting the association between anemia and IIH, the relationship remains controversial. Age- and sex-matched case controls by Giuseffi et al (9).…”
mentioning
confidence: 67%
“…The literature has previously documented variable prevalence of anemia in IIH patients, ranging from 7.5% to 32% (Table 2). A meta-analysis by Yu et al (8) reported a prevalence of 20.1%, which is similar to the 22.8% prevalence in the present study (8). Our finding that IIH patients have a higher likelihood of anemia than age-and sexmatched controls supports the findings of Yu et al (8) (RR 1.44, 95% CI 1.08, 1.92) and Ardissino et al (7) (OR 1.478, P , 0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…Cases with co-existent morbidities known to cause optic disc swelling or IIH were excluded, e.g., ischemic optic neuropathy or Leber’s Hereditary Optic Neuropathy, even if they also had nutritional deficiencies. We also excluded cases with iron deficiency and/or severe anaemia (defined as haemoglobin < 8.0 g/dL) [ 13 ] as they are already established risk factors for IIH and have been reviewed elsewhere [ 11 , 14 ]. Reports of epidemic optic neuropathy, e.g., the Cuban epidemic, were not included as individual patient-level information was lacking and there is still some uncertainty about their etiology; these cases are considered in the discussion.…”
Section: Methodsmentioning
confidence: 99%